Metafora synestezyjna w rosyjskich tekstach krytyki muzycznej - Dzienisiewicz, Maria (Acta Polono-Ruthenica, 2018)
The paper presents a variety of synesthetic metaphors used by musical critics. The metaphors were retrieved from musical critical texts written in Russian, which described classical music events. The basis of division are human senses: hearing, touch, sight and taste. Metaphors are divided into two main groups: intermodal and singlemodal ones. The most representative type turned out to be synesthetic metaphors referring to the sense of touch.